The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-022-30840-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaming up main group metals with metallic iron to boost hydrogenation catalysis

Abstract: Hydrogenation of unsaturated bonds is a key step in both the fine and petrochemical industries. Homogeneous and heterogeneous catalysts are historically based on noble group 9 and 10 metals. Increasing awareness of sustainability drives the replacement of costly, and often harmful, precious metals by abundant 3d-metals or even main group metals. Although not as efficient as noble transition metals, metallic barium was recently found to be a versatile hydrogenation catalyst. Here we show that addition of finely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…As we noted previously, [11] MVS-activated Fe 0 is a potent catalyst for 1-hexene reduction but di-substituted alkenes are clearly less reactive and tri-substituted alkenes show no conversion at all (Table 2, entries 1-2, 4, 8). This is in agreement with the generally reported poor activities of nanoparticulate Fe 0 in alkene hydrogenation (Scheme 2, right).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…As we noted previously, [11] MVS-activated Fe 0 is a potent catalyst for 1-hexene reduction but di-substituted alkenes are clearly less reactive and tri-substituted alkenes show no conversion at all (Table 2, entries 1-2, 4, 8). This is in agreement with the generally reported poor activities of nanoparticulate Fe 0 in alkene hydrogenation (Scheme 2, right).…”
Section: Methodssupporting
confidence: 71%
“…[7] c) Alkene hydrogenation with main group metal hydrides, [M]-H, catalyzed by the Fe 0 surface. [11] The role of Fe 0 is the activation of alkene and/or H 2 .…”
Section: Stoichiometric Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most challenging aspect of H 2 activation is the cleavage of the nonpolar H–H σ-bond . Although two-electron oxidative addition is well-established for late-transition-metal-mediated H 2 splitting, there is a growing interest to activate H 2 through metal–ligand cooperation. , Recently, bifunctional H 2 activation over TM–LA (LA = Lewis acid) bonds has emerged and attracted considerable attention. However, there is no precedent involving H 2 activation with early main-group metalloligand-based complexes . Therefore, we examined the reactivity of Mg–Ni–Mg complex 2 toward dihydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently we showed that finely divided metallic Fe 0 , which itself is a poor hydrogenation catalyst, converts polar main group metal hydrides into highly active catalysts for reduction of challenging alkenes and aromatic arenes [11] . Based on various observations, previous investigations on Ba 0 hydrogenation catalysts, [12] and old reports by Weller and Wright, [13] this boost in catalytic activity has been explained by a model in which the Fe 0 surface activates the alkene or arene for insertion (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%